Public journalism 2.0 : the promise and reality of a citizen-engaged press - Rosenberry, Jack; St. John, Burton, 1957- (Routledge, 2010)
Examines the ways that civic or public journalism is evolving, especially as audience-created content - sometimes referred to as citizen journalism or participatory journalism - becomes increasingly prominent in contemporary media. This book seeks to reinvent public journalism for the 21st century.